KEWARISAN GAJI PENSIUN PEGAWAI NEGERI SIPIL DI INDONESIA DALAM PERSPEKTIF MADZHAB SYAFI’I - Bahar, Alexsander; Ishaq; Muhammad Faisol (Al-Majaalis : Jurnal Dirasat Islamiyah, 2024)
Among the advantages of being a civil servant (PNS) is that the government guarantees that it will provide a monthly salary after the PNS retires. This salary is known as the PNS pension salary. In fact, when the retired employee dies, the pension salary can be transferred to his/her spouse if he/she is still alive, if he/she has died, it can be transferred to his/her child with the provisions stated in the Law. Then the question arises, is it right from a fiqh perspective if the distribution of the pension salary is transferred to certain people according to the Law, or does the pension salary become an inheritance that is divided based on Islamic inheritance law? This study aims to answer this question from the perspective of the Syafi'i school of thought, considering that this school of thought is the school of thought adopted by the majority of the Indonesian people. The method applied in this study is a qualitative method, with a descriptive approach. In collecting data, the author used library research techniques and interviews with some employees who work at PT. Taspen. PT Taspen is a business entity that manages PNS pension funds. The results of this study are that the salary of retired civil servants is not included in the inheritance, and those who are entitled to receive the salary after the death of the retired civil servant are the people listed in the Law that regulates the pension salary, in the order stated therein.